Naturphilosophie Redivivus: on Bruno Latour's 'Political Ecology' - Wilding, Adrian (Cosmos and History: The Journal of Natural and Social Philosophy, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Bruno Latour's work is at present having a remarkable influence upon theoretical work in the social sciences, yet in philosophical circles it remains largely unknown. The present paper aims to redress this somewhat, addressing in particular how Latour's thinking impacts on philosophical accounts of the relation between human subjectivity and the natural world. As part of what he calls his ‘political ecology', Latour's work challenges philosophers to rethink conceptions of nature bequeathed by post-Kantian philosophy in fundamental and novel ways. At the same time, as will be argued, Latour's thinking often unwittingly reworks moves within the tradition of Naturphilosophie, particularly motifs from Schelling's thought. Once the elective affinities between Latour's work and the German philosophical tradition are brought to light, one can see a failure on his part to deal fully with the sophisticated insights of Naturphilosophie – particularly as formulated by Schelling and, more radically, by Hegel – and that this tradition can be drawn upon to expose weaknesses in Latour's own arguments. Whilst Latour offers a compelling challenge to rethink notions of subject and object, free-will and mechanism, along with the conceptual separation of humans from nature, his thinking often fails to achieve the genuine critique that would be adequate to his own task: of comprehending humanity's relation to nature in order to find a way out of the our ecological crisis.